2021
DOI: 10.1097/tp.0000000000003975
|View full text |Cite
|
Sign up to set email alerts
|

Six-month Antibody Kinetics and Durability in SARS-CoV-2 mRNA Vaccinated Solid Organ Transplant Recipients

Abstract: This research was made possible with the generous support of the Ben-Dov family. This work was supported by the ASTS Fryer Resident Scientist Award

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…The study found 67% of SOT recipients to have anti-spike IgG antibodies in 4 months after the first dose ( 35 ). Alejo et al ( 27 ) reported data with 7 months of follow-up after the first dose of BNT162b2 or mRNA-1273 vaccine and found 72% of SOT recipients to have anti-spike IgG antibodies. We found 36% of SOT recipients to have a positive humoral response 6 months after the first vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found 67% of SOT recipients to have anti-spike IgG antibodies in 4 months after the first dose ( 35 ). Alejo et al ( 27 ) reported data with 7 months of follow-up after the first dose of BNT162b2 or mRNA-1273 vaccine and found 72% of SOT recipients to have anti-spike IgG antibodies. We found 36% of SOT recipients to have a positive humoral response 6 months after the first vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, while inferior immune responses in SOT recipients have been reported, little is known about risk factors for humoral and cellular non-response ( 5 , 6 , 10 18 , 27 , 34 , 35 ). We found increasing age, being less than 1 year from transplantation, use of mycophenolate or corticosteroids, being kidney or lung transplant recipient, and de novo non-skin cancer to be associated with humoral non-response 6 months after the first vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding patients who were seronegative and turned seropositive, we cannot rule out a delayed antibody response for SOT recipients, as also suggested by the two studies described above [ 25 , 26 ]. Peak antibody response has been previously demonstrated at between Day 15 and 45 after natural infection [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 96%
“…At ∼1 month following a second dose of mRNA vaccine, 63% were seropositive; at ∼3 months, 72% were seropositive; and at 6 months, 72% as well. Seven percent of seropositive patients at 1 month became seronegative at 6 months [ 26 ].…”
Section: Discussionmentioning
confidence: 99%